Preventing vessel perforations in endovascular thrombectomy: feasibility and safety of passing the clot with a microcatheter without microwire: the wireless microcatheter technique. (7th December 2018) - Keulers, Annika; Nikoubashman, Omid; Mpotsaris, Anastasios; Wilson, Scott D; Wiesmann, Martin
Abstract : Background: To place a stent retriever for thrombectomy in acute ischemic stroke, the clot has to be passed first. A microwire is usually used for this maneuver. As an alternative, a wireless microcatheter can be used to pass the clot. Objective: To analyze the feasibility and complication rates of passing the clot using either a microwire or a wireless microcatheter. Methods: A retrospective non-randomized analysis of 110 consecutive patients with acute ischemic stroke in the anterior circulation was performed, in whom video recordings of mechanical thrombectomies were available. In total, 203 attempts at mechanical recanalization were performed. Results: Successful recanalization (TICI 2b–3) was achieved in 97.3% of patients. In 71.8% of attempts the clot was successfully passed using a wireless microcatheter only. When a microwire was used initially, clot passage was successful in 95.3% of attempts. Complication rates for angiographically detectable subarachnoid hemorrhage were 6.1% when a microwire was used to pass the clot compared with 0% when a wireless microcatheter was used (p<0.001). Complication rates for angiographically occult circumscribed subarachnoid contrast extravasation observed on post-interventional CT scans were 18.2% when a microwire was used to pass the clot and 4.5% when a wireless microcatheter was used (p<0.001). Conclusions: In most cases of mechanical recanalization the clot can be passed with a wireless microcatheter instead of a microwire. In our study this method significantly reduced the risk for vessel perforation and subarachnoid hemorrhage. We therefore recommend the use of this technique whenever possible.